Ethical guidelines for occupational health professionals : an Africa Working Group perspective - London, Leslie; Tangwa, Godfrey; Matchaba-Hove, Reginald; Mkhize, N.; Nwabueze, Remi; Nyika, Aceme; Westerholm, Peter (2016)
The need for ethical guidelines in occupational health is widely recognised as key to good occupational health practice. Efforts by the International Commission on Occupational Health (ICOH) to update its Ethical Code led to the establishment of a Code Review Group (CRG) to which was affiliated an Africa Working Group to develop input to the ICOH Code revision process from an African perspective. The work of the group, over the past three years, has identified a number of key challenges for ethical occupational health practice in the region. This report summarises the trajectory of the groups’ discussions and identifies areas for further action if occupational health practice in Africa is to deliver on its promise of protecting and promoting the health of working populations across the globe.